Dual energy CT in gout: a prospective validation study. Issue 9 (2nd March 2012) - Choi, Hyon K; Burns, Lindsay C; Shojania, Kamran; Koenig, Nicole; Reid, Graham; Abufayyah, Mohammed; Law, Genevieve; Kydd, Alison S; Ouellette, Hugue; Nicolaou, Savvas
Abstract : Objective: The authors prospectively determined: (1) the specificity and sensitivity of dual energy CT (DECT) for gout; and (2) the interobserver and intraobserver reproducibility for DECT urate volume measurements. Methods: Forty crystal-proven gout patients (17 tophaceous) and 40 controls with other arthritic conditions prospectively underwent DECT scans of all peripheral joints using a gout protocol that color-codes the composition of tissues. A blinded radiologist identified urate deposition to calculate specificity and sensitivity of DECT for gout. Inter-rater volumetric reproducibility was determined by two independent radiologists on 40 index tophi from the 17 tophaceous gout patients using automated software. Results: The mean age of the 40 gout patients was 62 years, the mean gout duration was 13 years and 87% had a history of urate-lowering therapy (ULT). The specificity and sensitivity of DECT for gout were 0.93 (95% CI, 0.80 to 0.98) and 0.78 (0.62 to 0.89), respectively. When the authors excluded three gout cases with unreadable or incomplete scans, the sensitivity was 0.84 (95% CI, 0.68 to 0.94). The urate volumes of 40 index tophi ranged from 0.06 cm 3 to 18.74 cm 3 with a mean of 2.45 cm 3 . Interobserver and intraobserver intraclass correlation coefficients for DECT volume measurements were 1.00 (95% CI, 1.00 to 1.00) and 1.00 (95% CI, 1.00 to 1.00) with corresponding bias estimates (SD) of 0.01 (0.00) cm 3 and 0.01 (0.03) cm 3 . Conclusions: These prospective data indicate high reproducibility of DECT urate volume measures. The specificity was high, but sensitivity was more moderate, potentially due to frequent ULT use in our patients.